2021
DOI: 10.1002/ccd.29756
|View full text |Cite
|
Sign up to set email alerts
|

Real world outcomes using 20 mm balloon expandable SAPIEN 3/ultra valves compared to larger valves (23, 26, and 29 mm)–a propensity matched analysis

Abstract: Objective/Background: Small balloon expandable valves have higher echocardiographic transvalvular gradients and rates of prosthesis-patient mismatch (PPM) compared to larger valves. However, the impact of these echocardiographic findings on clinical outcomes is unknown. We sought to determine the clinical outcomes of 20 mm SAPIEN 3 (S3 BEV) compared to larger S3 BEV in relation to echocardiographic hemodynamics.Methods: Using the STS/ACC transcatheter valve registry, we performed a propensity-matched compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In our study, significant impact of severe PPM on mortality was observed in IAV and BEV, but not in SEV cohort. These findings collide with previous results from PARTNER 3 trial, which seemed to suggest no prognostic relevance of PPM after Sapien 3 implantation, 11 recently confirmed in a high‐numerosity propensity‐matched cohort of patients treated with BEV 21 . On the other hand, severe PPM did predict mortality in the CoreValve US High‐Risk trial, 9 even though this was not confirmed in a recent analysis of 47,620 patients from the Transcatheter Valve Therapy registry 10 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our study, significant impact of severe PPM on mortality was observed in IAV and BEV, but not in SEV cohort. These findings collide with previous results from PARTNER 3 trial, which seemed to suggest no prognostic relevance of PPM after Sapien 3 implantation, 11 recently confirmed in a high‐numerosity propensity‐matched cohort of patients treated with BEV 21 . On the other hand, severe PPM did predict mortality in the CoreValve US High‐Risk trial, 9 even though this was not confirmed in a recent analysis of 47,620 patients from the Transcatheter Valve Therapy registry 10 .…”
Section: Discussionmentioning
confidence: 62%
“…These findings collide with previous results from PARTNER 3 trial, which seemed to suggest no prognostic relevance of PPM after Sapien 3 implantation, 11 recently confirmed in a high-numerosity propensitymatched cohort of patients treated with BEV. 21 On the other hand, severe PPM did predict mortality in the CoreValve US High-Risk trial, 9 even though this was not confirmed in a recent analysis of 47,620 patients from the Transcatheter Valve Therapy registry. 10 Reasons behind the described selective prognostic impact of severe PPM might include derivation of echocardiographic mean gradients from transaortic velocity, and are being addressed.…”
Section: Ppm and All-cause Mortalitymentioning
confidence: 94%
“…Twenty-millimeter-diameter balloon-expandable valves used in patients with small annuli and aortas are known to be associated with higher discharge Doppler MG >20 mm Hg, yet are associated with similar survival compared with larger valve sizes. 4 Furthermore, correlation between Doppler and invasive pressure measurement may vary depending on the type of transcatheter valve. Balloon-expandable valves are observed to have higher MG by Doppler, yet lower invasive MG compared with self-expanding valves.…”
mentioning
confidence: 99%